Impact of Enhanced recovery after surgery (ERAS) protocols in idiopathic scoliosis of children: A systematic review with meta-analysis and trial sequential analysis - Soumya Sarkar; Bharat Yalla; Bhavuk Garg; Puneet Khanna (Indian Journal of Anaesthesia)
Background and Aims: Enhanced recovery after surgery (ERAS) protocols are widely adopted in various surgeries to improve outcomes and reduce length of stay (LOS). However, their cost-effectiveness in spine surgery for children is unclear. Methods: Studies comparing ERAS with conventional pathways for spinal surgery in children with idiopathic scoliosis were included after scrutiny of electronic databases (PubMed, Medline, and Embase), Google Scholar, preprint, and clinical trial databases after the protocol was enroled in PROSPERO (ID: CRD42023418323). Results: Twenty-five studies, including 15,399 patients, were included. Patients in the ERAS group had a significant reduction in LOS by −1.68 days [95% confidence interval (CI): −1.88, −1.47; I2 = 96%), per-patient hospital cost by 3765.27 USD, as per 2023 valuation (95% CI: −5257.43, −2273.12, I2 = 99.96%), risk of complications (log-odds ratio: −0.85; 95% CI: −1.45, −0.27; I2 =50.4%), blood loss by 159.38 mL (95% CI: 121.8, 197.79, I2 = 95.02%), compared to the traditional protocol group. On multivariable meta-regression analyses, the LOS was not impacted by age (P = 0.382), duration of surgery (P = 0.289), preoperative Cobb’s angle (P = 0.405), and intraoperative blood loss (P = 0.525). The required information size estimated for a power of 95% based on the 30% reduction in the LOS, 50% relative risk reduction for complications, reduction of per patient hospital cost of USD 3500 as per 2023 valuation, and reduction of mean intraoperative blood loss of 100 mL were 8599, 904, 499, and 499 respectively, was achieved. Conclusion: ERAS protocols in children’s scoliosis surgeries significantly reduce treatment costs through decreased hospital stays, fewer complications, and less intraoperative blood loss.